2010
DOI: 10.1007/s10750-010-0538-7
|View full text |Cite
|
Sign up to set email alerts
|

Otolith trace element and stable isotopic compositions differentiate fishes from the Middle Mississippi River, its tributaries, and floodplain lakes

Abstract: Naturally occurring stable isotope and trace elemental markers in otoliths have emerged as powerful tools for determining natal origins and environmental history of fishes in a variety of marine and freshwater environments. However, few studies have examined the applicability of this technique in large river-floodplain ecosystems. This study evaluated otolith microchemistry and stable isotopic composition as tools for determining environmental history of fishes in the Middle Mississippi River, its tributaries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 56 publications
4
51
0
1
Order By: Relevance
“…Missouri rivers possess distinct multivariate chemical signatures that can be used to identify natal environment and reconstruct inter-river movement patterns of fishes (Zeigler and Whitledge 2011;Phelps et al 2012). Differences in stable oxygen isotope ratios between the Illinois River and its floodplain lakes also enable identification of fish use of floodplain lake habitats (Zeigler and Whitledge 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Missouri rivers possess distinct multivariate chemical signatures that can be used to identify natal environment and reconstruct inter-river movement patterns of fishes (Zeigler and Whitledge 2011;Phelps et al 2012). Differences in stable oxygen isotope ratios between the Illinois River and its floodplain lakes also enable identification of fish use of floodplain lake habitats (Zeigler and Whitledge 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Combined analysis of elemental composition and Sr isotopic ratio could successfully associate individual fish with each sampling location with a high level of accuracy (mean 89%). High variability in otolith chemistry based on geographical differences in habitat location has been reported for several freshwater fish species (Gibson-Reinemer et al 2009, Pangle et al 2010, Zeigler & Whitledge 2011. If otolith chemistry can determine the natal or nursery area of an individual fish, it could also reveal the early dispersal patterns of fish in later stages of life.…”
Section: Discussionmentioning
confidence: 99%
“…The year-round outflow from San Francisco Bay may have generated the distinctive trace element signatures and high reclassification success at sites along the coast nearby, such as Abalone Point. Previous research has shown that all of the elements we sampled can vary among different freshwater sources due to natural and anthropogenic factors (Ouyang et al 2006, Zeigler & Whitledge 2011, creating particularly distinctive trace element signatures in areas influenced by freshwater runoff. The sites near San Francisco Bay experience terrestrially derived, anthropogenically influenced waters year-round, creating stability in the embryo trace element signatures, particularly of cobalt and copper, which are tracers of San Francisco Bay outflow (Hurst & Bruland 2008).…”
Section: Discussionmentioning
confidence: 99%